Estrategias didácticas y habilidades sociales en niños de preparatoria de la Escuela de Educación Básica Andrés Machado Montero de la ciudad de Loja, periodo 2023-2024 - Bustamante Bustamante, Mariuxi Tatiana (2024)
Social skills are abilities that help with interaction in one's environment, enabling effective handling of social and emotional situations. They assist in establishing meaningful connections, communicating effectively, and addressing problems constructively. Therefore, it is essential to foster the development of these skills from an early age, as it is fundamental for children to acquire necessary tools that will enable them to navigate autonomously and adaptively in their environment. This research aims to determine how didactic strategies help improve social skills in high school children at the Andrés Machado Montero Basic Education School in the city of Loja. A quasi-experimental design was used to manipulate the independent variable. Additionally, it employed a mixed approach, allowing for analysis, inquiry, and data collection. It had a descriptive scope and utilized inductive-deductive methods, enabling concrete analysis, providing meaning and structure to the work. Likewise, the analytic-synthetic method facilitated the construction of the theoretical framework. The instrument used was the Children and Adolescents Evaluation System Test (SENA), administered to a population of sixteen children, which revealed that 5.38% were often, always, or almost always at the level of social skills development. After implementing activities based on didactic strategies, the final evaluation showed that 87.25% increased their social levels. This demonstrates that didactic strategies such as play, theater, dance, storytelling, and drawing promote the development of social skills, allowing children to communicate with their peers, share materials, acquire habits of order, active listening, and teamwork. Keywords: Dance, storytelling, drawing, social skills, play, theater